Narrative Research Study: Market Sentiment As A Trigger For Cryptocurrency Volatility - Hidayatullah, Mahdi; Juniar, Asrid (SENTRALISASI, 2025)
This study aims to analyze the impact of market sentiment on cryptocurrency price volatility, focusing on the top 50 cryptocurrencies by market capitalization in 2024. Data was collected from CoinMarketCap for the period 2021-2023, and market sentiment is measured using Natural Language Processing on text data from social media (Twitter, Reddit), forums, and news articles. The analysis employs Structural Equation Modeling - Partial Least Squares to examine the relationship between market sentiment and price volatility. The latent variable "Market Sentiment" is constructed using the NLP indicator, while "Price Volatility" is measured by daily standard deviations and the Average True Range. Additional factors, such as Layer-1, Layer-2, Decentralized Finance, Specialized Computing, Real World Assets, and Decentralized Infrastructure Projects, are also incorporated for a more comprehensive analysis. The results show that positive sentiment significantly increased price volatility, especially for speculative projects like Layer-2 and DeFi, while negative sentiment significantly reduced volatility. Neutral sentiment had no significant effect on price volatility. These findings highlight the important role of social media and news in driving sharp price movements in the cryptocurrency market, providing valuable insights for investors and policymakers in managing and responding to market sentiment.